Endorsing voice behavior can be as devastating as rejecting it when the endorsement is laced with a hint of anger - Felipe A. Guzman; Antonella Tempesta Fernández; Melvyn R. W. Hamstra (Scientific Reports)
Abstract Voice endorsement—managers’ approval of employees’ voiced suggestions—has largely been regarded as positive, yet little research examines how managers’ emotional expressions during endorsement affect employees. Drawing on the Emotions as Social Information (EASI) model, we propose that not all instances of voice endorsements are necessarily positive events for employees. Specifically, we propose that managers’ anger while endorsing voice, negatively impact employees’ perceptions of psychological safety and their future voice behavior. Across two experimental studies, we find that participants who faced an angry manager endorsing their voice reported both lower psychological safety and future voice behavior than those whose voice was endorsed by a happy or neutral looking manager. Study 2 further found that employees experiencing voice endorsement with anger felt as psychologically unsafe as those whose voice was outright rejected, suggesting that anger-laden endorsements are just as detrimental as voice rejections. Our findings contribute to the literature by challenging the notion that all voice endorsements are inherently positive, emphasizing the role of managers’ emotions on managerial reactions to voice.